Georges Gusdorf e a autobiografia - Hervot, Brigitte Monique [UNESP] (My University, 2013)
Considering the premise that there are few theoretical reflections in the Portuguese language, concerning the autobiography as a genre, we propose to present a work addressing this issue by discussing the writings of George Gusdorf (1912-2000). One of the most expressive French scholars on this field, alongside Philippe Lejeune and Jean George May, and Starobinsky, Gusdorf stands out for his vast production centered on theoretical issues concerning the writings of the self. The study presented here aims at disseminating Gusdorf writings in Brazil, as well as presenting a critical analysis of the most pertinent issues related to the autobiographical genre, including aspects such as its origins, the blurred boundaries of genre, truth and sincerity, the relations between time and memory, self-knowledge and knowledge of the world.

Partindo da premissa de que existe uma carência de reflexões teóricas acerca da autobiografia, em língua portuguesa, propomo-nos elaborar um trabalho abordando esse tema por meio da obra de Georges Gusdorf (1912-2000), um dos estudiosos franceses mais expressivos nesse campo, que, ao lado de Philippe Lejeune, Georges May e Jean Starobinsky, se destaca pela sua vasta produção teórica centralizada na questão das escritas do eu. Esse estudo visa difundir a obra do autor no Brasil, bem como proceder a uma análise crítica das questões mais pertinentes relativas ao gênero autobiográfico, tais quais as origens e os limites imprecisos do gênero, a verdade e a sinceridade, o tempo e a memória, o autoconhecimento do sujeito e o conhecimento do mundo.
Georges Gusdorf and the autobiography
Keywords: Georges Gusdorf; Autobiografia; Escritas do eu; Georges Gusdorf; Autobiography; Writings of the self